A Model of Prevention of Sports Concussion in Adults - Lo, Chuling; Sirmon-Taylor, Bess (Seminars in Speech and Language, 2014)
This article discusses the definitions of prevention and presents a model that addresses multidimensional aspects of sports concussion prevention from the perspectives of epidemiology, education, environmental modification, enforcement, and evaluation. Epidemiology is helpful in identifying the incidence of concussion and the interventions most likely to reduce its occurrence. Education ensures that accurate information on concussion is communicated to stakeholders. Modifications in the physical and sociocultural environments may lessen the potential for injury and reduce the risk of concussion. Enforcement of legislation standards can be effective in concussion prevention, especially at the preinjury and injury phases. The evaluation dimension assesses the effectiveness of prevention programs and guides future program development. This five-E model explains concussion prevention as a recursive loop process. Each dimension is closely associated in the prevention of sports concussion.
Keywords: Sports concussion; prevention; five-E